Structure-guided optimization of D-captopril for discovery of potent NDM-1 inhibitors. (1st January 2021) - Ma, Guixing; Wang, Sanshan; Wu, Kebin; Zhang, Weizhe; Ahmad, Ashfaq; Hao, Quan; Lei, Xiaoguang; Zhang, Hongmin
Graphical abstract: New scaffolds were designed based on NDM-1/D-captopril structure and several compounds showed high inhibition potency and new interaction modes. Abstract: β-lactam antibiotics have long been the mainstay for the treatment of bacterial infections. New Delhi metallo-β-lactamase 1 (NDM-1) is able to hydrolyze nearly all β-lactam antibiotics and even clinically used serine-β-lactamase inhibitors. The wide and rapid spreading of NDM-1 gene among pathogenic bacteria has attracted extensive attention, therefore high potency NDM-1 inhibitors are urgently needed. Here we report a series of structure-guided design of D-captopril derivatives that can inhibit the activity of NDM-1 in vitro and at cellular levels. Structural comparison indicates the mechanisms of inhibition enhancement and provides insights for further inhibitor optimization.